On some toxinological aspects of the starfish Stellaster equestris (Retzius, 1805) - Kanagarajan,U (2008)
Whole-body extracts in methanol were obtained from the starfish Stellaster equestris. The crude toxin was fractionated stepwise using diethylaminoethyl (DEAE) cellulose column chromatography. The crude toxin was lethal to male albino mice at a dose of 1.00 mL (containing 531.0 µg/mL protein) when injected intraperitoneally (IP) but the toxicity was abolished in all cases except one upon fractionation. The crude toxin and all the adsorbed fractions exhibited potent hemolytic activity on chicken, goat and human blood. However, group B human erythrocytes were resistant to lysis by all fractions and group O by most of the fractions. Paw edema in mice was caused by the crude toxin and all fractions. Pheniramine maleate and piroxicam blocked the toxicity when administered earlier than, or along with, the crude or fractionated toxins but not when administered after the envenomation. Pretreatment with either of these drugs also blocked edema formation.